Antimicrobial effects and mechanical properties of poly(methyl methacrylate) as an orthodontic acrylic resin containing Curcumin-Nisin-poly(l-lactic acid) nanoparticle: an in vitro study - Maryam Pourhajibagher; Mohammad Noroozian; Mohammad Sadegh Ahmad Akhoundi; Abbas Bahador (BMC, 2022)
Abstract Background The porous surface of acrylic orthodontic removable appliances creates a niche for microbial plaque accumulation, and changes the oral flora by raising cariogenic bacteria including Streptococcus mutans. In this study, we evaluated the mechanical properties and antimicrobial activities of incorporating different concentrations of Curcumin-Nisin-poly(l-lactic acid) nanoparticle (CurNisNps) into orthodontic acrylic resin against Streptococcus mutans and Candida albicans. Methods Following synthesis and characterization of CurNisNps, acrylic resin specimens with different concentrations of CurNisNps (0, 1, 2, 5, and 10% w/w) were fabricated. Flexural strength values, antimicrobial effects, anti-biofilm potential, and anti-metabolic activity against S. mutans and C. albicans were assessed at different time intervals. Also, the expression of the virulence-factor-related genes of S. mutans and C. albicans was assessed by quantitative real-time polymerase chain reaction following treatment with CurNisNps. Results Acrylic resin containing 10% CurNisNps (30.76 ± 3.91 MPa) showed flexural failure in comparison with acrylic resin specimens without CurNisNps (50.67 ± 1.82 MPa) as the control group (P < 0.05). There was no significant decrease in the flexural strength values in samples containing 1, 2, and 5% of CurNisNps in comparison to the control group (P > 0.05). Acrylic resin with 5% CurNisNps showed the highest concentration of CurNisNps and clinically accepted flexural strength value (14.89 ± 3.26 MPa, P < 0.05) simultaneously. In the disc agar diffusion assay, 5% CurNisNps showed a high level of inhibitory activity for the test microorganisms. The reduction of growth inhibition zones of the different concentrations of CurNisNps against test microorganisms was positively associated with the time, in such a way that it was reduced significantly after 60 days. The anti-biofilm and anti-metabolic activities of acrylic resin specimens containing a 5% concentration of CurNisNps against S. mutans and C. albicans could significantly decrease the expression levels of gtfB (6.8-fold) and HWP (3.4-fold) in S. mutans and C. albicans, respectively. Conclusions Our data support that 5% (w/w) of CurNisNps can serve as an excellent orthodontic acrylic resin additive against S. mutans and C. albicans biofilm without adverse effects on its mechanical property.